Purification and characterization of bacteriocin produced by weissella confusa A3 of dairy origin - Goh, H.F.; Philip, K. (Public Library of Science, 2015)
A dramatic increase in bacterial resistance towards currently available antibiotics has raised worldwide concerns for public health. Therefore, antimicrobial peptides (AMPs) have emerged as a promisingly new group of therapeutic agents for managing infectious diseases. The present investigation focusses on the isolation and purification of a novel bacteriocin from an indigenous sample of cow milk and it’s mode of action. The bacteriocin was isolated from Weissella confusa A3 that was isolated from the sample and was shown to have inhibitory activity towards pathogenic bacteria namely Bacillus cereus, Escherichia coli, Pseudomonas aeruginosa and Micrococcus luteus. The bacteriocin was shown to be heat stable and functioned well at low pH (2 to 6). Reduction of activity was shown after treatment with proteinase K, trypsin and peptidase that confirmed the proteinaceous nature of the compound. MALDI-TOF analysis of the sample gave a mass approximating 2.7 kDa. The membrane of the bacteria was disrupted by the bacteriocin causing SYTOX® green dye to enter the cell and bind to the bacterial DNA giving fluorescence signal. Bacterial cell treated with the bacteriocin also showed significant morphological changes under transmission electron microscope. No virulence and disease related genes can be detected from the genome of the strain.